EXPORT PERFORMANCE OF GRAPES IN INDIA - A.D. SATHYENDRA KUMAR*; M. DEVARAJ (The Journal of Research ANGRAU, 2020)
The study(2018-19) focused on the export performance of fresh grapes in India during pre-WTO and post- WTO period and destination- wise growth rate from 2001-02 to 2016-17.To analyse the export data and arrive at appropriate results, Growth Rate analysis, Instability analysis and Markov Chain analysis were used.The results indicated that the export of fresh grapes with the pre-WTO and post-WTO period when compared, the growth rate of post-WTO period decreased in terms of quantity, value and unit value of export. However,the overall growth rate was positive. The Netherlands, The United Kingdom, The United Arab Emirates, Bangladesh and Germany are major importers of fresh grapes from India, and these countries have a positive growth rate during the study period. The results of the Transitional Probability Matrix of fresh grapes export from India showed that The Netherlands was one of the stable markets of Indian fresh grapes as reflected by the probability of retention.It might be due to increasing demand for fresh grapes in that country and as a crop it was not cultivated extensively in the Netherlands. However, Germany did not continue as a loyal importer of India’s fresh grapes. It might be due to rigid competition by other countries such as the Netherlands.